(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Food would be impossible to fathom without a packet It may be fresh-from-the-farm cereals,processed food from a high-tech company, or just cow’s milk. Food packaging can be found almostanywhere. Packaging, being a huge industry, has its own set of concepts, technologies, benefits anddrawbacks, processes, harmful effects, and costs. Furthermore, it is a rapidly evolving technology thathas progressed from basic paper and cardboard packaging to space-age intelligent packaging systems.It took more than 300 years for food packaging to reach its current state. Since then, a variety of packingmaterials have been used. Each type of packaging material has a distinct purpose in the packingprocess. Also, packaging materials such as biodegradable or edible packaging may meet the world’sdemand for natural and environmentally friendly meals, which is a major worldwide problem today. Withthe introduction of novel food packaging technologies such as active packaging, aseptic packaging,smart packaging, bioactive packaging, and edible packaging, which are research trends, the foodpackaging business has changed to a large extent in recent years.